The Impact of Artificial Intelligence on Literary Criticism: Exploring Potentials and Limitations - Muhammad, Muhammad Husein Hasan (Dzil Majaz: Journal of Arabic Literature, 2025)
This research aims to explore the impact of artificial intelligence (AI) on literary criticism, focusing on the potentials it offers and the challenges it faces in this field. With the advancement of AI technologies, it has become possible to analyze literary texts in innovative ways, opening unprecedented horizons for understanding literature. However, there is a need to evaluate how these technologies interact with traditional critical approaches and whether they can enrich or constrain literary criticism. The study adopts a descriptive-analytical methodology, utilizing AI tools such as sentiment analysis, linguistic and literary pattern recognition, and natural language processing (NLP) to analyze a selected corpus of Arabic literary texts (poetry, novels, and prose). The results of AI-driven analysis are then compared with traditional critical readings of the same texts to assess the accuracy and effectiveness of AI. The findings reveal that AI holds significant potential in analyzing large volumes of text quickly and accurately, as well as identifying recurring literary patterns that may be difficult for humans to detect. However, the technology faces notable challenges, such as its limited ability to comprehend complex cultural and historical contexts, and its lack of the creative and interpretive depth characteristic of human criticism. The research concludes that AI can serve as a supportive tool for literary critics but cannot replace human creativity in criticism. It recommends developing AI tools that account for the cultural and linguistic specificities of Arabic literature and encouraging critics to integrate technology with traditional methods to enhance the critical process